Dynamic scene occlusion culling in architectural scenes - 377884 Paunoo, Baldeve; Daut Daman; Nadzari Shaari; National Conference on Computer Graphics and Multimedia (2nd : 2004 : Bangi, Selangor) (Skudai : Universiti Teknologi Malaysia, 2004)
57